Konsep Gaya Hidup Berkelanjutan pada Kegiatan P5 (Proyek Penguatan Profil Pelajar Pancasila) dalam Perspektif Al-Qur'an Surah Al-Baqarah Ayat 30 - Radhita Azzahra; Abdur Razzaq; Kristina Imron (Journal on Education, 2024)
The Pancasila Learner Profile Strengthening Project or P5 is a program implemented by Merdeka Curriculum that focuses on learning through problem solving. We associate this program with the Perspective of Surah Al-Baqarah verse 30, which has a strong connection with the Sustainable Lifestyle Theme. This theme teaches students responsibility and care for the environment and utilizes waste into useful items. In line with Surah Al-Baqarah Verse 30, which shows the duty of humans as khalifah by not doing damage. The research uses the Library Research Method with data collection techniques from journals, articles, and books, that has been carried out. This method of analysis is guided again into Descriptive Analysis. From this research, the author found several things in the P5 Program in the Perspective of Surah Al-Baqarah Verse 30: human duty as Caliph, balance of needs and damage, knowledge and wisdom in managing resources, and environmental ethics. Students are expected to be able to apply the characters built in their duties as responsible Caliphs.